Trans-splicing correction of tau isoform imbalance in a mouse model of tau mis-splicing - Avale, Maria Elena (2013)
Abnormal metabolism of the tau protein is central to the pathogenesis of a number of dementias, including Alzheimer's disease. Aberrant alternative splicing of exon 10 in the tau pre-mRNA resulting in an imbalance of tau isoforms is one of the molecular causes of the inherited tauopathy, FTDP-17. We showed previously in heterologous systems that exon 10 inclusion in tau mRNA could be modulated by spliceosome-mediated RNA trans-splicing (SMaRT). Here, we evaluated the potential of trans-splicing RNA reprogramming to correct tau mis-splicing in differentiated neurons in a mouse model of tau mis-splicing, the htau transgenic mouse line, expressing the human MAPT gene in a null mouse Mapt background. Trans-splicing molecules designed to increase exon 10 inclusion were delivered to neurons using lentiviral vectors. We demonstrate reprogramming of tau transcripts at the RNA level after transduction of cultured neurons or after direct delivery and long-term expression of viral vectors into the brain of htau mice in vivo. Tau RNA trans-splicing resulted in an increase in exon 10 inclusion in the mature tau mRNA. Importantly, we also show that the trans-spliced product is translated into a full-length chimeric tau protein. These results validate the potential of SMaRT to correct tau mis-splicing and provide a framework for its therapeutic application to neurodegenerative conditions linked to aberrant RNA processing.